2021
DOI: 10.1002/rse2.200
|View full text |Cite
|
Sign up to set email alerts
|

21 000 birds in 4.5 h: efficient large‐scale seabird detection with machine learning

Abstract: We address the task of automatically detecting and counting seabirds in unmanned aerial vehicle (UAV) imagery using deep convolutional neural networks (CNNs). Our study area, the coast of West Africa, harbours significant breeding colonies of terns and gulls, which as top predators in the food web function as important bioindicators for the health of the marine ecosystem. Surveys to estimate breeding numbers have hitherto been carried out on foot, which is tedious, imprecise and causes disturbance. By using UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Recent studies have shown the promise of UAVs and deep learning for posture tracking [74][75][76] , semi-automatic detection of large mammals 42,77 , birds 78 , and, in low-altitude flight, even identification of individuals 79 . Drones are agile platforms that can be deployed rapidly-theoretically on demand-and with limited cost.…”
Section: New Sensors Expand Available Data Types For Animal Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the promise of UAVs and deep learning for posture tracking [74][75][76] , semi-automatic detection of large mammals 42,77 , birds 78 , and, in low-altitude flight, even identification of individuals 79 . Drones are agile platforms that can be deployed rapidly-theoretically on demand-and with limited cost.…”
Section: New Sensors Expand Available Data Types For Animal Ecologymentioning
confidence: 99%
“…As an example, large mammal detection in the Kuzikus reserve in 2014 was improved significantly by improving the detection methodologies, from a recall rate of 20% 35 to 80% 37 (for a common 75% precision rate). Finally, studies involving human operators demonstrated that ML enabled massive speedups in complex tasks such as individual and species recognition 38,39 and large-scale tasks such as animal detection in drone surveys 40 . Recent advances in ML methodology could accelerate and enhance various stages of the traditional ecological research pipeline (see Fig.…”
mentioning
confidence: 99%
“…Alternatively, one can attempt to process the entire image using a deep network and try to predict the density of animals or probability of finding animals within subregions of the image. This approach was taken by Kellenberger et al (2021) where they predict probability maps for seabirds within input images using a variant of the ResNet architecture. These maps are then processed to localize individual seabirds within the image.…”
Section: Related Work From Scientific Literaturementioning
confidence: 99%
“…Nowadays, aerial surveys are among the standard non-invasive approaches for tracking the marine mega fauna [6][7][8][9][10]. Those surveys consist of flight sessions over the…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining models which 102 are robust to such kind of noise is one of the most difficult challenges in marine 103 animal detection. Due to the complexity of detecting marine animals in those various scenarios, 105 research studies in the literature often limit their scope to the detection of a single animal 106 species [7,9] and/or to images with high density of animal instances [8,10]. For instance, 107 in the early work of [7], the authors tackle the detection of dugongs in aerial images 108 by combining an unsupervised region proposal method with a classification CNN.…”
mentioning
confidence: 99%